PENERAPAN MANAJEMEN RISIKO DALAM MEMINIMALISIR KLAIM PRODUK JAMINAN BANK GARANSI PADA PERUSAHAAN ASURANSI DI PROVINSI RIAU - Prama Widayat (Politeknik Negeri Bengkalis, 2018)
The research was conducted to observe the implementation of risk management in analyzing the contractor before issuing Surety Bond guarantee by the insurance and continue as the basis for the issuance of Bank Guarantee (KGB) by private banks and BUMN, because there are still contractors who do not perform their obligation to finish the work causing the claim bank guarantee product. The study was conducted by direct interviews to underwriting insurance issuing Bank Guarantee Cons (KGB) products. The study population amounted to about 67 insurance companies registered in Riau province. But not all of them publish KGB is only 5 general insurance companies, the determination of the number of samples is done by using the sampling area.